Pengembangan Media Pembelajaran Busy Book pada Materi Tema 6 Subtema 4 Kelas III di SD Negeri 10104481 Alur Baung T.A 2022/2023 - Nurafriani Dwi Agnesta; Laurensia Masri Perangin-Angin; Demmu Karo-Karo; Elvi Mailani; Husna Parluhutan Tambunan (FKIP, Universitas Palangka Raya, 2024)
This study aims to determine the feasibility, practicality, and effectiveness of busy book learning media in learning themes 6 sub-themes 4 learning 1 class III at SD Negeri 10104481 Alur Baung, Karang Baru District, Aceh Tamiang Regency. This type of research is research and development using 4D mode by Thiagarajan. The instruments used were questionnaire validation sheets, test validation sheets, material expert validation sheets, media expert validation sheets, interview sheets, education specialist (teacher) questionnaires, as well as pre-test and post-test. The results of research related to feasibility show that the results of material experts give an average value of 86% which is categorized as